2012
DOI: 10.1080/13603124.2011.624643
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between teachers’ and principals’ decision-making power: is it a win-win situation or a zero-sum game?

Abstract: Is the power relationship between public school teachers and principals a win-win situation or a zero-sum game? By applying hierarchical linear modeling to the 1999-2000 nationally representative Schools and Staffing Survey data, we found that both the winwin and zero-sum-game theories had empirical evidence. The decision-making areas characterized by the win-win theory are much more than those characterized by the zero-sum-game theory. The practice of win-win is more prevalent at the elementary than at the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…Shen and his colleague (J. Shen & Xia, 2012;Xia & Shen, 2019) used the nationally representative data from the NECS Schools and Staff Survey to study the power relationship between the principal and teachers in seven decision making areas: 'set performance standards,' 'establish curriculum,' 'determine content of professional development,' 'evaluate teachers,' 'hire new fulltime teachers,' 'set discipline policy,' and 'decide how to spend school budget'. Their multiple level modeling indicated that the power relationship between the principal and their teachers was characterized by win-win theory in all decision-making areas, except for the area of 'evaluating teachers'.…”
Section: Integrated Leadership As a Zero-sum Game Or A Win-win Situatmentioning
confidence: 99%
“…Shen and his colleague (J. Shen & Xia, 2012;Xia & Shen, 2019) used the nationally representative data from the NECS Schools and Staff Survey to study the power relationship between the principal and teachers in seven decision making areas: 'set performance standards,' 'establish curriculum,' 'determine content of professional development,' 'evaluate teachers,' 'hire new fulltime teachers,' 'set discipline policy,' and 'decide how to spend school budget'. Their multiple level modeling indicated that the power relationship between the principal and their teachers was characterized by win-win theory in all decision-making areas, except for the area of 'evaluating teachers'.…”
Section: Integrated Leadership As a Zero-sum Game Or A Win-win Situatmentioning
confidence: 99%
“…Hussain et al (2017) show that decisions made by principals influence the teacher and school performance. Shen and Xia (2012) also suggest that the principal's decision regarding teacher teaching policies in the classroom, the allocation of teacher working hours, school budget allocation, learning outcomes assessment issues and teacher assignments will specifically affect teacher performance. Poor decision-making by principals can lead to low teacher morale which is indicated by absenteeism and late arrival (Wadesango, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(C5) […] Hemos creado herramientas para la auto-refl exión docente, pero me falta poder para decirle al profesorado: 'es que tú lo haces porque, si no, estás incumpliendo una parte de tu trabajo'. (C8) Este comentario también refl eja un estilo de liderazgo solitario en la que muestra un tipo de relación con el profesorado difícil y una forma de defi nir la autoridad del director centralizando el poder (Lumby, 2013;Shen y Xia, 2012). De todas formas, aunque los directores sean conscientes de que en sus manos tienen el poder de ejercer su autoridad de forma centralizada, pues desde la administración educativa queda establecido así, ellos comprenden que ésta no es la forma de hacer progresar al centro y relacionarse con el profesorado, por tanto son partidarios de ejercer una "autoridad moral" sin imponer las cosas de manera coercitiva e intentando potenciar un sistema de relación no jerárquico.…”
Section: Resultsunclassified
“…El poder y la autoridad del director deben ser compartidos entre todos los miembros de la organización propiciando un cambio de las relaciones de poder (Shen y Xia, 2012), aunque teniendo muy presente que esto no signifi ca atacar su autoridad formal ni negar la infl uencia de los directores (Harris, 2013), pues como destaca Day (2009), los buenos directores no son carismáticos o heroicos en el sentido tradicional pero tienen un sentido muy resolutivo de su propósito moral y presentan características personales que permiten modelar a la gente y ser un patrón de referencia.…”
Section: El Rol Y Fi Gura Del Director Del Centrounclassified